2012
DOI: 10.1128/mcb.00151-12
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for DNA-Binding Domain–Ligand-Binding Domain Communications in the Androgen Receptor

Abstract: DNA binding as well as ligand binding by nuclear receptors has been studied extensively. Both binding functions are attributed to isolated domains of which the structure is known. The crystal structure of a complete receptor in complex with its ligand and DNA-response element, however, has been solved only for the peroxisome proliferator-activated receptor ␥ (PPAR␥)-retinoid X receptor ␣ (RXR␣) heterodimer. This structure provided the first indication of direct interactions between the DNA-binding domain (DBD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
48
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 59 publications
1
48
0
Order By: Relevance
“…Since the LBD has a strong inhibitory effect on AR import, the data suggest that the T877A substitution weakens the repressive effect of the LBD on nuclear import of androgen-free AR. Thus, interdomain interactions, already known to be relevant to the transactivation function of AR (26,27,39) and detected by FRET in both the WT and T877A forms of AR (40), can play a role in regulating nuclear import as well. A combination of protein modeling and mutagenesis was used by the Claussens group to show that interdomain communication in AR also occurs between the LBD and DBD (39), and this type of interaction likely occurs in other nuclear receptors as well (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the LBD has a strong inhibitory effect on AR import, the data suggest that the T877A substitution weakens the repressive effect of the LBD on nuclear import of androgen-free AR. Thus, interdomain interactions, already known to be relevant to the transactivation function of AR (26,27,39) and detected by FRET in both the WT and T877A forms of AR (40), can play a role in regulating nuclear import as well. A combination of protein modeling and mutagenesis was used by the Claussens group to show that interdomain communication in AR also occurs between the LBD and DBD (39), and this type of interaction likely occurs in other nuclear receptors as well (41).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, interdomain interactions, already known to be relevant to the transactivation function of AR (26,27,39) and detected by FRET in both the WT and T877A forms of AR (40), can play a role in regulating nuclear import as well. A combination of protein modeling and mutagenesis was used by the Claussens group to show that interdomain communication in AR also occurs between the LBD and DBD (39), and this type of interaction likely occurs in other nuclear receptors as well (41). Whether the T877A substitution stabilizes a conformation that is similar to an androgen-induced state in WT AR or whether this AR variant adopts a unique structure remain an open question.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that the fulllength of AR can be S-sulfhydrated in the presence of H 2 S. H 2 S suppressing AR downstream gene expression without changing AR interaction with HSPs as well as nuclear localization suggests to us that H 2 S may directly target at AR-DBD. AR-DBD contains two cysteine-rich zinc finger modules (6). The first zinc finger is responsible for the recognition of AREs, whereas the second zinc finger is involved in DNA-dependent dimerization and the stabilization and specificity of DNA binding (8).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the development of CRPC are largely unclear, although AR signaling still plays important roles in CRPC (5). The AR consists of four structurally and functionally distinct domains, a poorly conserved N-terminal domain, a highly conserved DNA binding domain (DBD), a short hinge region, and a moderately conserved C-terminal ligand binding domain (6,7). The DBD of AR contains two cysteine 4-type zinc fingers, which enable the AR to specifically recognize androgen-responsive elements (AREs) (8).…”
mentioning
confidence: 99%
“…Nonetheless, allosteric communication between receptor domains has been demonstrated in GR and other NRs (11)(12)(13)(14)(15). Notably, depending on the precise DNA sequences bound by retinoid X receptor (RXR)-vitamin D receptor (VDR) heterodimers, distinct domains outside of their DBDs adopt alternative conformations or changed dynamics, indicative of long-range allosteric communication (11).…”
mentioning
confidence: 99%